ANALISIS FAKTOR-FAKTOR YANG BERPENGARUH TERHADAP PENURUNAN RISIKO KECELAKAAN KERJA - Aritonang, Febriola Nova Fitri; Amin, Mawardi; Susetyo, Budi (Wahana Teknik Sipil: Jurnal Pengembangan Teknik Sipil, 2023)
The construction process of the AKASA Serpong apartment building requires heavy equipment in the form of a tower crane to facilitate the construction work process, but in its implementation, there are still errors that cause work accidents. Factors causing work accidents such as human skills, geographical conditions, and crane instrumentation are the root of the problem, where the application of SOPs is not implemented properly and correctly. The purpose of the study was to analyze and identify the dominant factors that cause and minimize the risk of work accidents using quantitative descriptive methods conducted through interviews, perceptions of respondents, and questionnaire surveys of 60 workers at the research location, the results were analyzed using the SPSS version 24 program. The results showed that the crane instrumentation factor was more dominant, having a significance value of 0.000 <0.05. As for the t count, the value is 8.235> t table (2.003) so it is very influential on the performance measurement variable of the application of SOPs that are useful for reducing the risk of work accidents.